Femtosecond laser direct writing of a 3D microcantilever on the tip of an optical fiber sensor for on-chip optofluidic sensing. Issue 19 (30th August 2022) - Li, Changxu; Liu, Yi; Lang, Changpeng; Zhang, Yonglai; Qu, Shiliang
Abstract : A microcantilever is fabricated by femtosecond laser direct writing for on-chip optofluidic sensing. Abstract : Real-time detection of the concentration of input fluid is essential for optofluidic sensing, especially in the case of biochips and organ-on-a-chip systems. In this paper, a microcantilever structure that enables temperature and liquid concentration sensing was fabricated on the tip of the optical fiber by femtosecond laser direct writing (two-photon polymerization, TPP) technology. An open Fabry–Pérot interferometer (F–P) structure was formed between the end of the optical fiber and the cantilever, so the sensor becomes quite sensitive to the localized temperature, concentration and refractive index of the target liquids. The reasonable size parameters of the cantilever were determined by structural stress analysis and interference spectrum analysis. By integrating the fiber sensor with a microfluidic chip, an on-chip optofluidic sensing platform is developed, which shows high sensitivities of the temperature (92.7 pm °C −1 ), concentration (0.3287 nm (g L −1 ) −1 ), and refractive index (1385.819 nm RIU −1 ). The reported optofluidic sensing platform demonstrates reasonably high stability and satisfactory sensing effect, holding great promise for applications in lab-on-a-chip systems.